SAPPHO BETWEEN FRIENDS AND ENEMIES: SPECIFICS OF WIEW ON HUMAN RELATIONSHIPS - TURENKO, Vitalii (Linguistic and Conceptual Worldviews, 2024)
The article explores the dynamics of friendship and enmity within the framework of the legacy of the early Greek poetess Sappho. It establishes that, akin to other poets of the archaic era, she adhered to the principle of reciprocating friendship with friendship and enmity with enmity. Nevertheless, it is revealed that certain hostile connotations and fragments are not solely explained by a personal factor, such as the betrayal experienced in the Sappho fiasco, but also by the political power struggle on the island of Lesbos. The poetess distinctly opposed the tyranny that emerged post the aristocratic rule of her relatives, leading to sharp criticism of girls aligning with her political adversaries, which extended to matters of religious services. Her enmity is portrayed as more than mere "blind hatred"; rather, it embodies a nuanced sentiment intertwined with political, religious, and social beliefs. Betraying someone in her eyes equated to betraying oneself. The analysis unveils that in her poems, Sappho contemplated friendship on two planes: interpersonal and between gods and people. Relations with the gods, particularly Aphrodite and Artemis, exhibited a patronizing nature, offering assistance to the poet in various life situations. The argument is substantiated that the elucidation of friendly relations with girls is ambivalent, encompassing not only a friendly and intimate nature but also implicit ritual and social connotations.
Keywords: Sappho, early Greek poetry, friendship, enmity, archaic literature, φιλία, ἐχθρός